Effect of Learning Model Savi Assisted Media Kabaca (Calendar Picture Story) of Skills Reading Understanding of Stories - Rahmatsani, Lutfiana (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of Learning Model SAVI aided KABACA media on reading comprehension skills of fourth grade students of SD Negeri Keji 2 Muntilan, Magelang Regency. This research is a type ofresearch pre-experimental (One Group pretest posttest). The research subjects were selected by- nonprobability sampling saturated sampling model. Samples were taken as many as 24 students. The method of data collection was done by using test questions in the form of giving pretest and posttest reading comprehension skills. Test the validity of the pretest and posttest questions using theformula, product moment while the reliability test uses the formula Cronbach Alpha. The analysis prerequisite test used the normality test using theformula Kolmogorov-Smirnov. Data analysis used non-parametric statistical techniques Wilcoxon Sign rank test. The results of this study indicate that the calculation of the averagevalue posttest of 87 is greater than the averagevalue pretest of 57, this is evidenced by the results of thetest analysis Wilcoxon with thevalue Asymp. Sig. (2 tailed) obtained 0.000 <0.05 with a Z score of -4.297. Based on the data obtained, it is concluded that the SAVI learning model assisted by KABACA media has a positive effect on the reading comprehension skills of fourth grade students of SD Negeri Keji 2 Muntilan, Magelang Regency.